High-magnetism Sm2Co17 type sintered samarium-cobalt magnet and preparation method thereof
Through the controllable heating multi-stage tempering process of magnetic field-assisted magnetic deflection angle, the problems of the intrinsic coercive force and squareness of samarium-cobalt permanent magnet materials under high Fe content are solved, and the samarium-cobalt magnets are realized under high Fe content. High magnetic performance broadens the scope of application of Fe element addition.
Patent Information
- Application Number
- CN202411019397.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-31
AI Technical Summary
When the existing samarium-cobalt permanent magnet materials improve magnetic properties, excessive Fe elements lead to a decrease in intrinsic coercive force and squareness, and local laser heating and magnetic field treatment methods fail to effectively solve the problem of magnetic performance sharp drop caused by high Fe content. .
The temperature-raising multi-stage tempering process with controllable magnetic deflection angle is adopted to temper the solid solution magnet. The external magnetic field is used to promote element diffusion, and the solid solution magnet is transformed into 1:7H phase and 1:5H phase to improve cell shape. Organizational integrity.
The intrinsic coercive force and squareness of the magnet are maintained at high Fe content, widening the addition amount and magnetic properties of Fe elements of samarium-cobalt magnets, and significantly improving the overall performance of the magnet.
Smart Images

Figure CN119230230A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnetic material preparation, and in particular to a high-magnetism Sm2Co17 type sintered samarium cobalt magnet and a preparation method thereof. Background Art
[0002] Samarium cobalt magnets are widely used in defense, military industry, aerospace and many other fields due to their high Curie temperature, excellent magnetic properties, good temperature stability and excellent corrosion resistance. The improvement of the comprehensive magnetic properties of samarium cobalt permanent magnet materials is achieved by increasing the Fe content of the magnet, but excessive Fe elements will greatly reduce the intrinsic coercivity and squareness of the magnet. For example, when the Fe content is increased to 18.5%, the intrinsic coercivity of the magnet basically disappears, and the comprehensive magnetic properties deteriorate significantly. In order to improve the performance of samarium cobalt permanent magnet materials, such as Chinese patent 2024105904059, the invention name is a method for improving the high and low temperature shock resistance of samarium cobalt magnets. The finished samarium cobalt magnet is subjected to local laser heating and local magnetic field treatment. This method is for the aging state magnet that has been tempered. Heating and magnetic field are used to accelerate the aging of the magnet surface in advance, stabilize the elements on the magnet surface, and then stabilize the magnetic properties of the magnet when used in a complex environment. However, this method will reduce the magnetic properties of the treated magnet area, and does not solve the problem of sudden drop in magnetic properties caused by high Fe content. Therefore, it is necessary for technicians in this field to design a high-magnetic Sm2Co17 type sintered samarium cobalt magnet that can have good intrinsic coercivity while ensuring Fe content and comprehensive performance. Summary of the invention
[0003] In order to achieve the above object, the present invention provides the following technical solutions:
[0004] The present invention provides a method for preparing a high-magnetic Sm2Co17 type sintered samarium cobalt magnet, comprising the following preparation steps:
[0005] (1) weighing raw materials according to the mass ratio of each element in the Sm(CoFeCuZr)z alloy, mixing them, and then performing vacuum induction melting to prepare an alloy ingot;
[0006] (2) The alloy ingot is subjected to coarse and medium crushing to obtain coarse magnetic powder, and then fine magnetic powder is obtained by air jet milling or ball milling;
[0007] (3) subjecting the fine magnetic powder to magnetic field orientation and cold isostatic pressing to form a compact;
[0008] (4) sintering and solution treating the compact;
[0009] (5) The solid solution magnet is tempered by a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain a high-magnetic Sm2Co17 sintered samarium cobalt permanent magnet material.
[0010] Furthermore, in step (1), the mass percentages of the elements in the Sm(CoFeCuZr)z alloy are as follows: Sm content is 24.5% to 26.5%; Fe content is 18.5% to 36.5%; Cu content is 1.5% to 2.5%; Zr content is 0.5% to 2.0%; and the remainder is Co.
[0011] Furthermore, the average particle size of the fine magnetic powder is 2.8 to 3.7 microns.
[0012] Furthermore, in step (3), the orientation magnetic field is 2 T, the cold isostatic pressing pressure is 350 MPa, and the cold isostatic pressing time is 5 min.
[0013] Furthermore, in step (4), the sintering temperature is 1190-1240° C., and the sintering time is 1-5 h; the solution temperature is 1140-1185° C., and the solution time is 2-9 h.
[0014] Furthermore, in step (4), the magnetic deflection angle of the solid solution magnet obtained is ≤5 degrees.
[0015] Furthermore, in step (5), the tempering step is to first place the solid solution magnet at 350-400 degrees Celsius for 2-8 hours, during which the angle between the easy magnetization axis of the magnet and the external magnetic field is 15-35 degrees, and the magnitude of the external magnetic field is 0.3T-0.6T;
[0016] Then the temperature is raised to 550-670 degrees Celsius and kept for 4-12 hours. During this stage, the angle between the easy magnetization axis of the magnet and the external magnetic field is 40-75 degrees, and the magnitude of the external magnetic field is 0.6T-0.8T.
[0017] The temperature is then raised to 790-850 degrees Celsius and kept for 9-15 hours. During this stage, the angle between the easy magnetization axis and the external magnetic field is 80-90 degrees, and the magnitude of the external magnetic field is 0.9T-1.2T.
[0018] The present invention also provides a high-magnetic Sm2Co17 type sintered samarium cobalt magnet, which is prepared by the above-mentioned high-magnetic Sm2Co17 type sintered samarium cobalt magnet preparation method.
[0019] The present invention has the following beneficial effects:
[0020] The present invention uses a magnetic field-assisted multi-stage tempering process with a controllable magnetic deflection angle to synchronously apply a magnetic field with a controllable angle during the tempering of the solid solution magnet, and uses an external magnetic field to promote the diffusion of elements inside the samarium cobalt magnet, and promote the transformation of the solid solution magnet 1:7H phase to the aging magnet 2:17R and 1:5H phase, thereby effectively solving the problem of incomplete cellular structure in high-Fe samarium cobalt, thereby greatly reducing the intrinsic coercive force and squareness of the magnet. The cellular structure of the magnet is still complete at a higher Fe content, and the coercive force H cj and knee coercivity H k It can still maintain a high level, further expanding the amount of Fe element added to the samarium cobalt magnet and the magnetic properties of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a cellular organization diagram of the magnet prepared in Example 1.
[0022] Figure 2 This is the cellular structure of the magnet prepared in Comparative Example 1-1. DETAILED DESCRIPTION
[0023] The specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. It should be pointed out that the embodiments are only specific explanations of the invention and should not be regarded as limitations of the invention. The purpose of the embodiments is to enable those skilled in the art to better understand and reproduce the technical solutions of the present invention. The protection scope of the present invention shall still be based on the scope defined by the claims.
[0024] Example 1
[0025] The highly magnetic Sm2Co 17 The type sintered samarium cobalt magnet is prepared by the following preparation method, and the specific preparation steps are:
[0026] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 25.5%, Fe = 27.5%, Cu = 2.0%, Zr = 1.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 min to make alloy ingots;
[0027] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0028] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0029] (4) sintering and solution treating the prepared green compact to obtain a solid solution magnet, wherein the sintering temperature is 1200° C. and the sintering time is 3 h; the solution treating temperature is 1175° C. and the solution treating time is 7 h;
[0030] (5) The solid solution magnet is treated with a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain high magnetic Sm2Co 17 The tempering process of the sintered samarium cobalt magnet is as follows: keep it at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 20 degrees, and the magnetic field size is 0.4T; then heat it to 630 degrees Celsius and keep it for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 60 degrees; the magnetic field size is 0.7T; then heat it to 835 degrees Celsius and keep it for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 85 degrees, and the magnetic field size is 1.2T.
[0031] Comparative Example 1-1 (the difference from Example 1 is that the tempering process adopts a multi-stage temperature rise tempering process and no magnetic field treatment is performed)
[0032] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0033] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 25.5%, Fe = 27.5%, Cu = 2.0%, Zr = 1.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0034] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0035] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0036] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0037] (5) The solid solution magnet is treated by a magnetic field heating multi-stage tempering process to obtain high magnetic Sm2Co 17 The process of sintering samarium cobalt magnet is as follows: keep the temperature at 380 degrees Celsius for 6 hours; then heat it to 630 degrees Celsius for 9 hours; then heat it to 835 degrees Celsius for 13 hours.
[0038] Comparative Example 1-2 (the difference from Example 1 is that the magnetic field treatment is not performed in the first stage of the tempering process)
[0039] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0040] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 25.5%, Fe = 27.5%, Cu = 2.0%, Zr = 1.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0041] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0042] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0043] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0044] (5) The solid solution magnet is treated with a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain high magnetic Sm2Co 17The process of sintered samarium cobalt magnet is as follows: keep at 380 degrees Celsius for 6 hours; then heat to 630 degrees Celsius for 9 hours, the angle between the applied external magnetic field and the easy magnetization axis is 60 degrees; the magnetic field size is 0.7T; then heat to 835 degrees Celsius for 13 hours, the angle between the applied external magnetic field and the easy magnetization axis is 85 degrees, and the magnetic field size is 1.2T.
[0045] Comparative Examples 1-3 (the difference from Example 1 is that the second stage of the tempering process does not undergo magnetic field treatment)
[0046] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0047] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 25.5%, Fe = 27.5%, Cu = 2.0%, Zr = 1.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0048] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0049] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0050] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0051] (5) The solid solution magnet is treated with a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain high magnetic Sm2Co 17 The process of sintered samarium cobalt magnet is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 20 degrees, and the magnetic field size is 0.4T; then heat to 630 degrees Celsius and keep warm for 9 hours; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 85 degrees, and the magnetic field size is 1.2T.
[0052] Comparative Examples 1-4 (the difference from Example 1 is that the third stage of the tempering process does not undergo magnetic field treatment)
[0053] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0054] (1) Alloy Sm(CoFeCuZr)z, calculated by mass percentage, Sm=25.5%, Fe=27.5%, Cu=2.0%, Zr=1.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45kw and a vacuum degree of less than 5*10-2Pa. After the metal is melted, it is refined for 10 minutes to form an alloy ingot.
[0055] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0056] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0057] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0058] (5) The solid solution magnet is treated with a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain high magnetic Sm2Co 17 The process of sintered samarium cobalt magnet is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 20 degrees, and the magnetic field size is 0.4T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 60 degrees, and the magnetic field size is 0.7T; then heat to 835 degrees Celsius and keep warm for 13 hours.
[0059] The high magnetic Sm2Co prepared in Example 1 and Comparative Examples 1-1, 1-2, 1-3 and 1-4 17 Type sintered samarium cobalt magnets for remanence B r , coercive force H cj , knee point coercivity H k and maximum magnetic energy product BH (max) The test data are shown in Table 1.
[0060] Table 1
[0061] sample <![CDATA[B r (kG)]]> <![CDATA[H cj (no)]]> <![CDATA[H k (no)]]> <![CDATA[BH (max) (MGOe)]]> Example 1 11.35 27.06 20.15 32.67 Comparative Example 1-1 9.19 24.60 13.83 28.21 Comparative Example 1-2 10.93 25.89 17.80 30.25 Comparative Examples 1-3 9.78 26.37 16.96 29.92 Comparative Examples 1-4 10.28 26.39 17.83 29.53
[0062] It can be seen from Table 1 that the comprehensive magnetic properties of the magnet prepared in Example 1 are significantly better than those of the magnets prepared in Comparative Examples 1-1, 1-2, 1-3 and 1-4;
[0063] By comparing Example 1 with Comparative Example 1-1, the H cj 27.06kOe, H k The H of the magnet prepared in Comparative Example 1-1 without magnetic field assisted magnetic deflection angle controllable temperature rise multi-stage tempering process cj 24.60kOe, H k It is 13.83kOe. It can be seen that the lack of a multi-stage tempering process with a controllable magnetic deflection angle assisted by a magnetic field makes the intrinsic coercivity and squareness of the samarium cobalt magnet unfavorable.
[0064] By comparing Example 1 with Comparative Examples 1-2, the magnets prepared in Comparative Examples 1-2 were not subjected to auxiliary magnetic field in the first stage multi-stage tempering process, and their H cj 25.89kOe, H k The value is 17.80 kOe, which is lower than the performance of the magnet obtained in Example 1, that is, the application of an auxiliary magnetic field in the first stage of the multi-stage tempering process with a controllable magnetic deflection angle assisted by a magnetic field can improve the intrinsic coercivity and squareness of the samarium cobalt magnet;
[0065] By comparing Example 1 with Comparative Examples 1-3, the magnets prepared in Comparative Examples 1-3 were not subjected to auxiliary magnetic field in the second stage multi-stage tempering process, and their H cj 26.37kOe, H k The value is 16.96 kOe, which is lower than the performance of the magnet obtained in Example 1, that is, the application of an auxiliary magnetic field in the second stage of the multi-stage tempering process with a controllable magnetic deflection angle assisted by a magnetic field can improve the intrinsic coercivity and squareness of the samarium cobalt magnet.
[0066] By comparing Example 1 with Comparative Examples 1-4, the magnets prepared in Comparative Examples 1-4 were not subjected to auxiliary magnetic field in the third stage multi-stage tempering process, and their H cj 26.39kOe, H k The value is 17.83 kOe, which is lower than the performance of the magnet obtained in Example 1, that is, the application of an auxiliary magnetic field in the third stage of the multi-stage tempering process with a controllable magnetic deflection angle assisted by a magnetic field can improve the intrinsic coercivity and squareness of the samarium cobalt magnet.
[0067] In summary, each stage of the magnetic field-assisted multi-stage annealing process with controllable magnetic deflection angle is essential for the preparation of magnets with high Fe content, high intrinsic coercivity and high squareness.
[0068] In addition, the cellular structure of the magnet prepared by Example 1 is as follows Figure 1As shown, the cell structure of the magnet prepared by comparative example 1-1 is as follows Figure 2 As shown, it can be clearly seen Figure 1 The cellular organization in Figure 2 Incomplete cellular structure appears in the magnet. Therefore, compared with the prior art, the present invention effectively solves the problem of incomplete cellular structure in high-Fe samarium-cobalt magnets, thereby greatly reducing the intrinsic coercive force and squareness of the magnet. The cellular structure of the magnet is still complete at a higher Fe content. cj and H k It can still maintain a high level, further expanding the amount of Fe element added to the samarium cobalt magnet and the magnetic properties of the magnet.
[0069] Example 2
[0070] The samarium cobalt magnet of this embodiment is prepared by the following steps:
[0071] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 26.5%, Fe = 36.5%, Cu = 2.5%, Zr = 2.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0072] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0073] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0074] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0075] (5) The solid solution magnet is treated with a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain high magnetic Sm2Co 17The process of sintered samarium cobalt magnet is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 15 degrees, and the magnetic field size is 0.3T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 40 degrees, and the magnetic field size is 0.6T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 80 degrees, and the magnetic field size is 0.9T.
[0076] Comparative Example 2-1 (the difference from Example 2 is that the auxiliary magnetic deflection angle in the first stage of the tempering process is 0)
[0077] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0078] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 26.5%, Fe = 36.5%, Cu = 2.5%, Zr = 2.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0079] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0080] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0081] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0082] (5) The solid solution magnet is subjected to a magnetic field-assisted multi-stage annealing process with controllable magnetic deflection angle to obtain a high magnetic Sm2Co17 type sintered samarium cobalt magnet. The process is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 0 degrees, and the magnetic field magnitude is 0.3T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 40 degrees, and the magnetic field magnitude is 0.6T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 80 degrees, and the magnetic field magnitude is 0.9T.
[0083] Comparative Example 2-2 (the difference from Example 2 is that the auxiliary magnetic deflection angle in the second stage of the tempering process is 0)
[0084] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0085] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 26.5%, Fe = 36.5%, Cu = 2.5%, Zr = 2.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0086] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0087] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0088] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0089] (5) The solid solution magnet is subjected to a magnetic field-assisted multi-stage annealing process with controllable magnetic deflection angle to obtain a high magnetic Sm2Co17 type sintered samarium cobalt magnet. The process is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 15 degrees, and the magnetic field magnitude is 0.3T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 0 degrees, and the magnetic field magnitude is 0.6T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 80 degrees, and the magnetic field magnitude is 0.9T.
[0090] Comparative Example 2-3 (the difference from Example 2 is that the auxiliary magnetic deflection angle in the third stage of the tempering process is 0)
[0091] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0092] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 26.5%, Fe = 36.5%, Cu = 2.5%, Zr = 2.0%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, mixed and subjected to vacuum induction melting at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0093] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0094] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0095] (4) Sintering and solution treatment are performed on the prepared compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3h; solution temperature is 1175°C, and solution time is 7h;
[0096] (5) The solid solution magnet is subjected to a magnetic field-assisted multi-stage annealing process with controllable magnetic deflection angle to obtain a high magnetic Sm2Co17 type sintered samarium cobalt magnet. The process is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 15 degrees, and the magnetic field magnitude is 0.3T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 40 degrees, and the magnetic field magnitude is 0.6T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 0 degrees, and the magnetic field magnitude is 0.9T.
[0097] The high magnetic Sm2Co prepared in Example 2, Comparative Example 2-1, Comparative Example 2-2 and Comparative Example 2-3 17 Type sintered samarium cobalt magnets for remanence B r , H cj , H k and BH (max) The test data are shown in Table 2.
[0098] Table 2
[0099] sample <![CDATA[B r (kG)]]> <![CDATA[H cj (no)]]> <![CDATA[H k (no)]]> <![CDATA[BH (max) (MGOe)]]> Example 2 10.02 26.20 17.54 29.21 Comparative Example 2-1 9.22 25.73 15.67 28.26 Comparative Example 2-2 10.33 25.24 17.27 29.42 Comparative Examples 2-3 9.26 26.10 13.52 27.48
[0100] It can be seen from Table 2 that the comprehensive magnetic properties of the magnet prepared in Example 2 are significantly better than those of the magnets prepared in Comparative Example 2-1, Comparative Example 2-2, and Comparative Example 2-3;
[0101] By comparing Example 2 with Comparative Example 2-1, the H cj 26.20kOe, H k The H of the magnet prepared in Comparative Example 2-1 is 17.54 kOe. cj 25.73kOe, H k It is 15.67kOe. It can be seen that in the multi-stage tempering process with controlled magnetic deflection angle assisted by magnetic field, the angle between the direction of the external magnetic field and the easy magnetization axis has an important influence on the intrinsic coercivity and squareness of the samarium cobalt magnet.
[0102] By comparing Example 2 with Comparative Example 2-2, in the preparation of Comparative Example 2-2 in the magnetic field-assisted magnetic deflection angle controllable temperature-raising multi-stage tempering process, the direction of the external magnetic field applied in the second stage is at an angle of 0 degrees with the easy magnetization axis direction, and the H of the magnet prepared by the magnet is cj 25.21kOe, H k It is 17.27kOe. It can be seen that in the multi-stage tempering process with controlled magnetic deflection angle assisted by magnetic field, the appropriate angle between the direction of the external magnetic field and the direction of the easy magnetization axis can improve the intrinsic coercive force and squareness of the samarium cobalt magnet;
[0103] By comparing Example 2 with Comparative Examples 2-3, in the preparation of Comparative Example 2-3 in the magnetic field-assisted magnetic deflection angle controllable temperature-raising multi-stage tempering process, the direction of the external magnetic field applied in the three stages is at an angle of 0 degrees with the easy magnetization axis direction, and the H of the magnet prepared by the magnet is cj 26.10kOe, H k It is 13.52kOe. This further proves that the angle between the external magnetic field direction and the easy magnetization axis direction in the multi-stage tempering process with controlled magnetic deflection angle assisted by magnetic field can improve the intrinsic coercivity and squareness of samarium cobalt magnets;
[0104] In the temperature-raising multi-stage tempering process, in order to obtain an Fe-content magnet with high intrinsic coercivity and high squareness, it is necessary to maintain a certain angle between the direction of the external magnetic field and the direction of the easy magnetization axis of the magnet.
[0105] Example 3
[0106] The samarium cobalt magnet of this embodiment is prepared by the following steps:
[0107] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 24.5%, Fe = 18.5%, Cu = 1.5%, Zr = 0.5%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, and the raw materials are mixed and vacuum induction melted at a power of 45 kW and a vacuum degree of less than 5*10-2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0108] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0109] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0110] (4) Sintering and solution treatment are performed on the prepared green compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3 hours; solid solution temperature is 1175°C, and solid solution time is 7 hours;
[0111] (5) The solid solution magnet is treated with a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain high magnetic Sm2Co 17 The process of sintered samarium cobalt magnet is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 35 degrees, and the magnetic field size is 0.6T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 75 degrees; the magnetic field size is 0.8T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 90 degrees, and the magnetic field size is 1.2T.
[0112] Comparative Example 3-1 (the difference from Example 3 is that the magnetic field size in the first stage of the tempering process is reduced)
[0113] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0114] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 24.5%, Fe = 18.5%, Cu = 1.5%, Zr = 0.5%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, and the raw materials are mixed and vacuum induction melted at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0115] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0116] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0117] (4) Sintering and solution treatment are performed on the prepared green compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3 hours; solid solution temperature is 1175°C, and solid solution time is 7 hours;
[0118] (5) The solid solution magnet is subjected to a magnetic field-assisted multi-stage annealing process with controllable magnetic deflection angle to obtain a high magnetic Sm2Co17 type sintered samarium cobalt magnet. The process is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 35 degrees, and the magnetic field magnitude is 0.15T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 75 degrees; the magnetic field magnitude is 0.8T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 90 degrees, and the magnetic field magnitude is 1.2T.
[0119] Comparative Example 3-2 (the difference from Example 3 is that the magnetic field size in the second stage of the tempering process is reduced)
[0120] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0121] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 24.5%, Fe = 18.5%, Cu = 1.5%, Zr = 0.5%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, and the raw materials are mixed and vacuum induction melted at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0122] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0123] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0124] (4) Sintering and solution treatment are performed on the prepared green compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3 hours; solid solution temperature is 1175°C, and solid solution time is 7 hours;
[0125] (5) The solid solution magnet is subjected to a magnetic field-assisted multi-stage annealing process with controllable magnetic deflection angle to obtain a high magnetic Sm2Co17 type sintered samarium cobalt magnet. The process is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 35 degrees, and the magnetic field magnitude is 0.6T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 75 degrees; the magnetic field magnitude is 0.3T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 90 degrees, and the magnetic field magnitude is 1.2T.
[0126] Comparative Example 3-3 (the difference from Example 3 is that the magnetic field size in the third stage of the tempering process is reduced)
[0127] The samarium cobalt permanent magnet material of this comparative example is prepared by the following steps:
[0128] (1) Alloy Sm(CoFeCuZr)z, in terms of mass percentage, Sm = 24.5%, Fe = 18.5%, Cu = 1.5%, Zr = 0.5%, and the remainder Co. The raw materials are weighed according to the mass ratio of the above elements, and the raw materials are mixed and vacuum induction melted at a power of 45 kW and a vacuum degree of less than 5*10 -2 Pa, after the metal is melted, it is refined for 10 minutes to make alloy ingots.
[0129] (2) The alloy ingot is coarsely crushed to obtain coarse powder, and then the coarse powder is processed by ball milling to obtain fine magnetic powder with an average particle size of 3.2 microns.
[0130] (3) The fine magnetic powder is subjected to magnetic field orientation and cold isostatic pressing to form a compact, wherein the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min; in the preparation process of the sintered magnet, anisotropic magnets can be obtained by orientation molding, and the cold isostatic pressing treatment can increase the density of the compact, which is conducive to sintering density;
[0131] (4) Sintering and solution treatment are performed on the prepared green compact to obtain a solid solution magnet, wherein the process is as follows: sintering temperature is 1200°C, sintering time is 3 hours; solid solution temperature is 1175°C, and solid solution time is 7 hours;
[0132] (5) The solid solution magnet is subjected to a magnetic field-assisted multi-stage annealing process with controllable magnetic deflection angle to obtain a high magnetic Sm2Co17 type sintered samarium cobalt magnet. The process is as follows: keep warm at 380 degrees Celsius for 6 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 35 degrees, and the magnetic field magnitude is 0.6 T; then heat to 630 degrees Celsius and keep warm for 9 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 75 degrees; the magnetic field magnitude is 0.8 T; then heat to 835 degrees Celsius and keep warm for 13 hours, the angle between the direction of the applied external magnetic field and the direction of the easy magnetization axis is 90 degrees, and the magnetic field magnitude is 0.5 T.
[0133] The high magnetic Sm2Co prepared in Example 3, Comparative Example 3-1, Comparative Example 3-2 and Comparative Example 3-3 17 Type sintered samarium cobalt magnets for remanence B r , H cj , H k and BH (max) The test data are shown in Table 3.
[0134] Table 3
[0135] sample <![CDATA[B r (kG)]]> <![CDATA[H cj (no)]]> <![CDATA[H k (no)]]> <![CDATA[BH (max) (MGOe)]]> Example 3 10.11 26.04 18.49 30.42 Comparative Example 3-1 9.22 25.63 15.46 28.82 Comparative Example 3-2 9.88 25.62 16.32 29.06 Comparative Example 3-3 9.93 26.32 15.34 28.55
[0136] It can be seen from Table 3 that the comprehensive magnetic properties of the magnet prepared in Example 3 are significantly better than those of the magnets prepared in Comparative Example 3-1, Comparative Example 3-2, and Comparative Example 3-3;
[0137] By comparing Example 3 with Comparative Example 3-1, the H cj 26.04kOe, H k The external magnetic field strength applied in the first stage of the preparation of the magnetic field-assisted magnetic deflection angle controllable multi-stage tempering process in Comparative Example 3-1 is 0.15T, and the H of the prepared magnet is cj 25.63kOe, H k That is, the comprehensive magnetic properties of the magnet with low magnetic field strength in the first stage of the multi-stage tempering process are lower than those of the magnet in Example 3.
[0138] By comparing Example 3 with Comparative Example 3-2, the external magnetic field strength applied in the second stage of the preparation of the magnetic field-assisted magnetic deflection angle controllable temperature-raising multi-stage tempering process in Comparative Example 3-2 is 0.3T, and the H of the magnet prepared by the cj 25.62kOe, H k That is, the comprehensive magnetic properties of the magnet with low magnetic field strength in the second stage of the multi-stage tempering process are lower than those of the magnet in Example 3.
[0139] By comparing Example 3 with Comparative Example 3-3, the external magnetic field strength applied in the third stage of the preparation of the magnetic field-assisted magnetic deflection angle controllable temperature-raising multi-stage tempering process in Comparative Example 3-3 is 0.5T, and the H of the magnet prepared by the magnet is cj 26.32kOe, H k That is, the comprehensive magnetic properties of the magnet with low magnetic field strength in the third stage of the multi-stage tempering process are lower than those of the magnet in Example 3.
[0140] From the above, it can be seen that in the temperature-raising multi-stage tempering process, in order to obtain an Fe-content magnet with high intrinsic coercive force and high squareness, the direction of the external magnetic field needs to maintain a certain angle with the direction of the easy magnetization axis of the magnet, and the external magnetic field also needs a certain magnetic field strength.
[0141] Finally, the remanence Br, Hcj, Hk and BH(max) of the high magnetic Sm2Co17 type sintered samarium cobalt magnets prepared in Example 1, Example 2 and Example 3 were tested. The data are shown in Table 4.
[0142] Table 4
[0143] sample <![CDATA[B r (kG)]]> <![CDATA[H cj (no)]]> <![CDATA[H k (no)]]> <![CDATA[BH (max) (MGOe)]]> Example 1 11.35 27.06 20.15 32.67 Example 2 10.02 26.20 17.54 29.21 Example 3 10.11 26.04 18.49 30.42
[0144] By comparing the magnetic properties of the magnets prepared in Example 1, Example 2 and Example 3, it can be seen that the magnets prepared by this invention method all have good magnetic properties. By using a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle, a magnetic field with a controllable angle is applied synchronously during the tempering of the solid solution magnet, and an external magnetic field is used to promote the diffusion of elements inside the samarium cobalt magnet, and promote the transformation of the solid solution magnet 1:7H phase to the aged magnet 2:17R and 1:5H phase, which effectively solves the problem of incomplete cellular structure in high-Fe samarium cobalt, thereby greatly reducing the intrinsic coercivity and squareness of the magnet. The cellular structure of the magnet is still complete at a higher Fe content, and the coercivity H cj and knee coercivity H k It can still maintain a high level, further expanding the amount of Fe element added to the samarium cobalt magnet and the magnetic properties of the magnet.
[0145] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0146] It should be noted that the technical features not described in detail in the present invention can be implemented by any existing technology.
Claims
1. A method for preparing a high magnetic Sm2Co17 type sintered samarium cobalt magnet, characterized in that: The preparation steps include: (1) weighing raw materials according to the mass ratio of each element in the Sm(CoFeCuZr)z alloy, mixing them, and then performing vacuum induction melting to prepare an alloy ingot; (2) The alloy ingot is subjected to coarse and medium crushing to obtain coarse magnetic powder, and then fine magnetic powder is obtained by air jet milling or ball milling; (3) orienting the fine magnetic powder in a magnetic field and cold isostatic pressing the fine magnetic powder into a compact; (4) sintering and solution treating the compact; (5) The solid solution magnet is tempered by a magnetic field-assisted multi-stage tempering process with controllable magnetic deflection angle to obtain a final high-magnetic Sm2Co17 type sintered samarium cobalt permanent magnet material.
2. The method for preparing a high magnetic Sm2Co17 type sintered samarium cobalt magnet according to claim 1, characterized in that: In step (1), the mass percentages of the elements in the Sm(CoFeCuZr)z alloy are as follows: Sm content is 24.5% to 26.5%; Fe content is 18.5% to 36.5%; Cu content is 1.5% to 2.5%; Zr content is 0.5% to 2.0%; and the remainder is Co.
3. The method for preparing a high magnetic Sm2Co17 type sintered samarium cobalt magnet according to claim 1, characterized in that: The average particle size of the fine magnetic powder is 2.8 to 3.7 microns.
4. The method for preparing a high magnetic Sm2Co17 type sintered samarium cobalt magnet according to claim 1, characterized in that: In step (3), the orientation magnetic field is 2T, the cold isostatic pressing pressure is 350MPa, and the cold isostatic pressing time is 5min.
5. The method for preparing a high magnetic Sm2Co17 type sintered samarium cobalt magnet according to claim 1, characterized in that: In step (4), the sintering temperature is 1190-1240° C., and the sintering time is 1-5 hours; the solution temperature is 1140-1185° C., and the solution time is 2-9 hours.
6. The method for preparing a high magnetic Sm2Co17 type sintered samarium cobalt magnet according to claim 1, characterized in that: In step (4), the magnetic deflection angle of the obtained solid solution magnet is ≤5 degrees.
7. The method for preparing a high magnetic Sm2Co17 type sintered samarium cobalt magnet according to claim 1, characterized in that: In step (5), the tempering treatment step is to first place the solid solution magnet at 350-400 degrees Celsius for 2-8 hours, during which the angle between the easy magnetization axis of the magnet and the external magnetic field is 15-35 degrees, and the magnitude of the external magnetic field is 0.3T-0.6T; Then the temperature is raised to 550-670 degrees Celsius and kept for 4-12 hours. During this stage, the angle between the easy magnetization axis of the magnet and the external magnetic field is 40-75 degrees, and the magnitude of the external magnetic field is 0.6T-0.8T. The temperature is then raised to 790-850 degrees Celsius and kept for 9-15 hours. During this stage, the angle between the easy magnetization axis and the external magnetic field is 80-90 degrees, and the magnitude of the external magnetic field is 0.9T-1.2T.
8. A high magnetic Sm2Co17 type sintered samarium cobalt magnet, characterized in that: The high magnetic Sm2Co17 type sintered samarium cobalt magnet is prepared by the preparation method of any one of claims 1 to 7.
